An examination of the precipitation delivery mechanisms for Dolleman Island, eastern Antarctic Peninsula - Russell, A; Mcgregor, GR; Marshall, GJ (Tellus A, 2004)
Copyright @ 2004 Wiley-Blackwell The variability of size and source of significant precipitation events were studied at an Antarctic ice core drilling site: Dolleman Island (DI), located on the eastern coast of the Antarctic Peninsula. Significant precipitation events that occur at DI were temporally located in the European Centre for Medium-Range Weather Forecasting (ECMWF) reanalysis data set, ERA-40. The annual and summer precipitation totals from ERA-40 at DI both show significant increases over the reanalysis period. Three-dimensional backwards air parcel trajectories were then run for 5 d using the ECMWF ERA-15 wind fields. Cluster analyses were performed on two sets of these backwards trajectories: all days in the range 1979–1992 (the climatological time-scale) and a subset of days when a significant precipitation event occurred. The principal air mass sources and delivery mechanisms were found to be the Weddell Sea via lee cyclogenesis, the South Atlantic when there was a weak circumpolar trough (CPT) and the South Pacific when the CPT was deep. The occurrence of precipitation bearing air masses arriving via a strong CPT was found to have a significant correlation with the southern annular mode (SAM); however, the arrival of air masses from the same region over the climatological time-scale showed no such correlation. Despite the dominance in both groups of back trajectories of the westerly circulation around Antarctica, some other key patterns were identified. Most notably there was a higher frequency of lee cyclogenesis events in the significant precipitation trajectories compared to the climatological time-scale. There was also a tendency for precipitation trajectories to come from more northerly latitudes, mostly from 50–70°S. The El Niño Southern Oscillation (ENSO) was found to have a strong influence on the mechanism by which the precipitation was delivered; the frequency of occurrence of precipitation from the east (west) of DI increased during El Niño (La Niña) events.